Development of Independent Solar Energy Performance Monitoring System - Muhammad Radzi Abdul Hamid; Sim Sy Yi; Aira Zambri; Farahiyah Mustafa (Progress in Engineering Application and Technology, 2022)
Solar energy is one of the most ecologically safe energy resources, contributing nothing to global warming. The benefits of properly utilising solar energy are numerous. There is no cost except for the initial installation of the device. Malaysia has a wide range of renewable energy resources, including solar, biomass, and wind energy, among others. Solar energy has huge power generating potential; nevertheless, new incentives must be devised to boost its economic feasibility. In recent years, there has been a tremendous surge in the construction of solar plants all over the world. The total energy output and performance of solar plants are dependent on the proper and timely maintenance of various components such as solar panel strings, inverters, and transformers. These devices can deteriorate over time or as a result of specific equipment failing. The purpose of this project is to develop the solar energy system to enhance the energy management and efficiency contributing with internet of thing that can be monitoring on performance of the solar energy such as power output and energy. This system was tested by connecting the photovoltaic panel in parallel. As a result, the resultant current equals the sum of all the panels in the series. The overall voltage will be the same as a single panel’s output voltage. This approach does not need a series connection since it allows the panels to operate continuously even if one of panels fails.